LEARNING OF DIGITAL LITERACY FOR MEDIA FIGHTERS OF DA'WAH EDUCATIONAL INSTITUTIONS AL-BAHJAH CIREBON - Anggraini, Clara Novita (PPM Universitas Telkom, 2023)
Every year, the trend of internet users in Indonesia continues to increase. However, the increase in internet use is accompanied by an increase in the negative impact of digital media on society. For example, the inability to distinguish between credible information and fake news (hoax). Unfortunately, most of the hoaxes circulating are information that has a wedge with religion. Therefore, Telkom University in collaboration with the Al-Bahjah Da'wah Education Institute (LPD) organizes da'wah digital literacy learning for media activists called media fighters. LPD Al Bahjah media fighters are students who manage broadcast media as a means of digital da'wah. Media managed to include YouTube, Instagram, and radio. The training through material presentation and interactive discussion on Digital Literacy Skills was conducted on-site in the LPD Al-Bahjah Cirebon area. Based on the results of observations during this program activity, the digital da'wah literacy learning activities for LPD Al-Bahjah media fighters have been helpful in increasing knowledge and understanding, improving the digital literacy skills of da'wah for LPD Al-Bahjah media warriors at the cognitive level.